Learn Mac OS X Snow Leopard - Lee, Mike; Meyers, Scott (Apress : Imprint: Apress, 2009)
You're smart and savvy, but also busy. This comprehensive guide to Apple's Mac OS X 10.6, Snow Leopard, gives you everything you need to know to live a happy, productive Mac life. Learn Mac OS X Snow Leopard will have you up and connected lickity-split. With a minimum of overhead and a maximum of useful information, you'll cover a lot of ground in the time it takes other books to get you plugged in. If this isn't your first experience with Mac OS X, skip right to the "What's New in Snow Leopard" sections. You may also find yourself using this book as a quick refresher course or a way to learn new Mac skills you've never tried before.